2010
DOI: 10.3354/ab00256
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on growth, colony development and carbon partitioning in three Phaeocystis species

Abstract: ABSTRACT:Phaeocystis is an ecologically important marine phytoplankton genus that is globally distributed. We examined the effects of temperature on the 3 most common species: P. globosa, P. antarctica, and P. pouchetii, which grew at 16-32, 0-6, and 4-8°C, respectively. P. pouchetii did not form colonies; P. globosa formed colonies at 16, 20, and 24°C, and P. antarctica colonies were observed at all temperatures. More cells were partitioned into the colonial form at lower temperatures than at higher temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 60 publications
1
21
1
Order By: Relevance
“…While the colonial stage is always diploid, flagellates can be haploid or diploid (Peperzak & Gaebler-Schwarz, 2012). While traditionally nutrient supply and zooplanktonic grazing have been considered cues for colony formation, a recent culture study by Wang et al (2010) showed the colony size and the number of cells per colony decreased with increasing temperature in Phaeocystis antarctica Karsten 1905 and P. globosa Scherffel 1899, while Takabayashi et al (2006) found an increasing number of cells per chain at higher temperatures in the diatom Skeletonema costatum (Grevillle) Cleve 1873.…”
Section: Temperature Effects In Clonal Culturesmentioning
confidence: 99%
“…While the colonial stage is always diploid, flagellates can be haploid or diploid (Peperzak & Gaebler-Schwarz, 2012). While traditionally nutrient supply and zooplanktonic grazing have been considered cues for colony formation, a recent culture study by Wang et al (2010) showed the colony size and the number of cells per colony decreased with increasing temperature in Phaeocystis antarctica Karsten 1905 and P. globosa Scherffel 1899, while Takabayashi et al (2006) found an increasing number of cells per chain at higher temperatures in the diatom Skeletonema costatum (Grevillle) Cleve 1873.…”
Section: Temperature Effects In Clonal Culturesmentioning
confidence: 99%
“…This indicated that in addition to the environmental temperature and the content of silicate itself, the content of iron in environment played an important role in controlling the silicate utilization by diatom cells in some degree. Temperature is undoubtedly considered to be the main factor affecting algae growth [53]. For diatom, temperature not only affects the growth and photosynthesis of algae cells, but also affects the synthesis and accumulation of chemical constituents in cells [12].…”
Section: Coupling Effects Of Silicate Iron and Other Various Abioticmentioning
confidence: 99%
“…Solitary cell concentrations were measured using 1-ml Sedgwick-Rafter chambers. Colony concentration, colony size and cells per colony were measured in 24 multi-plates using a Nikon inverted microscope with a calibrated micro-ruler (Tang, 2003;Wang et al, 2010). Colonies were counted within 24 h of collection to limit colony disruption in the preserved state.…”
Section: Microscopy and Chlorophyll Determinationsmentioning
confidence: 99%
“…Prior to the experiments, solitary cells of the three strains of P. globosa were isolated by passing the culture through a 10-mm nylon sieve twice under gravity (Tang, 2003), and experiments were initiated with an initial solitary cell density of 10 4 cells ml À1 . Triplicate onelitre batch cultures of each strain were grown in f/2 medium with a salinity of 32 PSU, where NH þ 4 , NO 3 or urea were added as the nitrogen source with an initial N concentration of 8.82 Â 10 À4 M. All cultures were bubbled with filtered air to maintain a uniform distribution (Wang et al, 2010).…”
Section: Experimental Culturesmentioning
confidence: 99%
See 1 more Smart Citation